2017
DOI: 10.1101/136911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Functional Characterization of Human 21st Chromosome Orthologs inCaenorhabditis elegans

Abstract: Individuals with Down syndrome have neurological and muscle impairments due to an additional copy of the human 21 st chromosome (HSA21). Only a few of ~200 HSA21 genes encoding protein have been linked to specific Down syndrome phenotypes, while the remainder are understudied. To identify poorly characterized HSA21 genes required for nervous system function, we studied behavioral phenotypes caused by loss-offunction mutations in conserved HSA21 orthologs in the nematode Caenorhabditis elegans. We identified te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Recently, DONSON was found to encode a novel fork protein factor and play an important role in mammalian DNA replication and genome stability. Moreover, its mutation caused microcephalic dwarfism . Previous studies showed that DONSON is a member of replisome complex and protected stalled or damaged replication forks.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, DONSON was found to encode a novel fork protein factor and play an important role in mammalian DNA replication and genome stability. Moreover, its mutation caused microcephalic dwarfism . Previous studies showed that DONSON is a member of replisome complex and protected stalled or damaged replication forks.…”
Section: Discussionmentioning
confidence: 99%
“…Nordquist et al [49] contributed to the functional annotation of Hsa21 genes by analyzing locomotion, exploration, and feeding behavior in worms with knockout mutations in orthologs of 27 Hsa21 genes. This screen identified ten Hsa21 genes as candidates for neurodevelopmental phenotypes: SYNJ1, CBS, RUNX1, EVA1C, DONSON, N6AMT1, PDXK1, COL18A1, NCAM2, and POFUT2.…”
Section: Systematic Characterization Of Hsa21 Orthologs In C Elegansmentioning
confidence: 99%
“…Affected individuals often die perinatally due to incomplete lung development. A neuronal function was implied by altered movement patterns of Caenorhabditis elegans mutants featuring DONSON variants [26]. Since microcephaly, pre-and postnatal growth retardation, and skeletal abnormalities, especially radial ray defects, occur in both diseases some MISSLA patients have originally been diagnosed with Fanconi anaemia (FA) [21,24].…”
Section: Introductionmentioning
confidence: 99%